2015
DOI: 10.1080/02673843.2015.1014925
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating and media exposure among adolescent girls: the role of parental involvement and sense of empowerment

Abstract: Objectives: This study aimed to explore relations between disordered eating pathology (DEP), exposure to media messages and sense of empowerment in female adolescents. Additionally, it aimed to investigate parental involvement as related to their daughters' sense of empowerment. Method: Participants were 248 girls aged 12-19 who completed self-report questionnaires assessing demographic data, DEP, body image, exposure to media, sense of empowerment and parental involvement type. Results: Main results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 83 publications
(100 reference statements)
3
34
0
5
Order By: Relevance
“…For example, some studies established that the influence of the mother has more intense consequences on the development of body image among female adolescents, while in other studies, the influence of the father is found to be more important in development of body image 33 . Findings in our study are only partially in accordance with the mentioned results, since they point out that influence of the mother and the father on body image have equal contributions on body dissatisfaction among adolescents of both genders, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies established that the influence of the mother has more intense consequences on the development of body image among female adolescents, while in other studies, the influence of the father is found to be more important in development of body image 33 . Findings in our study are only partially in accordance with the mentioned results, since they point out that influence of the mother and the father on body image have equal contributions on body dissatisfaction among adolescents of both genders, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Media has long been known to have an important negative influence on adolescents’ body attitudes and appearance-related concerns (Thompson & Stice, 2001), and greater consumption of media has been found to be associated with reports of elevations in DE among young adolescents (Holland & Tiggemann, 2016; Latzer, Spivak-Lavi, & Katz, 2015; Thompson et al, 1999; Tiggemann, 2011). For example, in a systematic review of 20 studies that examined associations between social networking and body dissatisfaction or DE (Holland & Tiggemann, 2016), significant cross-sectional and longitudinal associations were described for adolescents and young adults (5 of 20 with a longitudinal component; 8 of 20 included only adolescents; 6 of 20 examined gender differences).…”
Section: A Biopsychosocial Model and The Tripartite Sociocultural Influence Modelmentioning
confidence: 99%
“…Finally, the co-occurrence of ARPIU and Sub-ED was associated with greater depression than either risk behavior independently. While the nature of the relationship between Sub-ED and ARPIU is unclear with respect to etiology and temporal progression, recent evidence suggests that more time spent on the Internet, specifically on Facebook, is associated with greater eating-disorder pathology (Latzer, Spivak-Lavi, & Katz, 2015; Mabe, Forney & Keel, 2014). Therefore, future research should explore the type of Internet use (e.g., online gaming or social media) that is problematic, specifically among those with co-occurring ARPIU and Sub-ED.…”
Section: Discussionmentioning
confidence: 99%